Morphological and Genetic Characteristics of Red Snapper (Lutjanidae) in Nabire Waters - Maharani, Andi Nacisa Malfin Savina; Sala, Ridwan; Toha, Abdul Hamid A; Purbani, Debora Christin; Mokodongan, Daniel Frikli; Kusuma, Aradea Bujana; Pranata, Bayu (Marine Science Department Diponegoro University, 2025)
The Lutjanidae family has a wide range of varieties, posing challenges in their morphological identification. Molecular identification is crucial for augmenting the current morphological data as a comprehensive database for documenting the presence of economically significant fish species in Nabire water. This article provides a comprehensive analysis of the morphological and genetic characteristics of red snapper species, as well as assessment of the evolutionary connections among snapper fish found in the water. This study aims to analyze the morphological and genetic characteristics of red snapper species and assess the evolutionary relationships among red snapper found in the sea waters. The DNA extraction procedure was conducted according to the instructions provided by the Geneaid gSYNC DNA extraction kit. The molecular marker used is the DNA barcode of the cytochrome oxidase subunit I (CO1) gene. A total of 29 individuals were identified, representing 8 species, namely Lutjanus timoriensis, Lutjanus gibbus, Lutjanus bohar, Lutjanus papuensis, Pinjalo lewisi, Etelis coruscans, Pristipomoides multidens, and Aphareus rutilans. The molecular analysis indicated that there was a fragment length of 620 base pairs (bp). P. multidens and L. gibbus had the greatest genetic distance (0.22), whilst the species L. bohar and L. gibbus had the smallest genetic distance (0.11). The phylogenetic tree reconstruction yielded 8 monophyletic clades. Based on morphological and genetic analysis, eight species of the Lutjanidae family were identified in Nabire waters. Research is needed on biological parameters such as size when first caught, optimum length of capture and size when first gonad mature.